63 Nocturia—An Underappreciated "Symptom" of Obstructive Sleep Apnoea?. (16th March 2021) - Yeong, K; Santiapillai, J; Arumainayagam, B N; Murray, P; Tadtayev, S
Abstract:  : Nocturia (>2 per night) is the most frequent cause of disturbed sleep in older people. Poor sleep results in reduced health related QoL, and is linked to the development of cognitive impairment. Nocturia can result in an increase risk of falls and fractures, and is also an independent risk factor for mortality. The prevalence of norturia is high in the elderly, and it has been reported to be around 77.1% in elderly women and 93% in men. Historically, this bothersome symptom is thought to be mainly a result of bladder outflow obstruction due to prostatic hypertrophy or overactive bladder. More recently, nocturia has been associated witsh nocturnal polyuria (NPu) and obstructive sleep apnoea (OSA). The relationship between OSA and NPu is not fully understood but it is thought that the negative intrathoracic pressure generated by OSA causes an increase in Atrial Natriuretic Peptide (ANP) secretion, resulting in NPu. Nocturia is highly prevalent in patients with severe OSA. However, patients are usually unaware that they have sleep apnoea, and are therefore more likely to present to urology or geriatric services. It is important that OSA is not overlooked in these clinics as intervention with CPAP is highly effective in reducing symptoms. Here, we present the result of using the STOP-Bang questionnaire in 71 consecutive patients presenting to our urology service with nocturia. The average age was 73 years (range 34-88), male-to-female ratio 14:1 and median nocturia frequency of 4. 42 patients were at risk of undiagnosed sleep apnoea (median STOP-Bang Score of 5)—35 were referred for sleep studies, 4 patients declined and 3 patients were not referred. Overall, 31 out of 35 sleep studies (88.6%) demonstrated the presence of OSA; of these 23 (74.2%) confirmed moderate or severe OSA. All patients with OSA were seen and treated by the respiratory service. Overall, median nocturia frequency decreased from 4 to 1 across the whole cohort, from a combination of CPAP therapy, bladder outlet procedures and desmopressin. Conclusion: At least a third of patients (32%) with bothersome nocturia have an undiagnosed clinically-significant OSA. Identification of OSA improves outcomes across the whole cohort, because nocturia in patients without OSA is more likely to respond to bladder outlet procedures and desmopressin.